G582(P) Operative note quality improvement – examining compliance with the royal college of surgeons of england guidelines in a paediatric general surgical unit. (27th April 2015) - Ryan, A; Reeves, T; Kuti, K; Flett, M
Abstract : Context: Operative notes should be documented " clearly, accurately and legibly " – as endorsed by the GMC's Good Medical Practice. The RCS Eng. Guidelines (2014) advocate contemporaneous, complete surgical records. This audit identified significant shortcomings in operative documentation amongst paediatric general surgical cases in a tertiary care centre. Data collection was performed by two FY1s and a Surgical Registrar. Problem: Surgical operation notes necessitate accurate documentation from both a medico-legal and professional perspective; whilst comprehensive records facilitate post-operative patient management. However; in practice they are frequently sub-standard, thus raising concerns towards patient safety. Current operative note templates within our unit fail to comply with relevant guidelines. Assessment of problem and analysis of its causes: We identified poorly-documented details within general surgical operation notes using a data collection tool incorporating pertinent, recently-published guidance. Areas for improvement included: patient's weight, type of procedure performed (i.e. emergency vs. elective), whether surgery was with or without complication, and antibiotic prophylaxis. Results attained were compared against data from previous audits of a similar nature (carried out in 2010 and 2011 respectively). Intervention: Our proposed intervention involves promoting typed documentation of operative notes, whilst advocating their transition from paper text to an electronic format. We plan to achieve this through usage of a unique, pre-existing computerised system developed by a consultant within the department, which additionally populates our current Trakcare system upon document creation. We hope to educate the entire general surgical team in its practice. Furthermore, we will introduce informative posters highlighting the RCS Eng. guidelines and reiterating imperative operative details within the main theatres and day surgery unit. Letters detailing the audit's key findings and our intended strategy for change were sent to all consultants and surgical trainees. Study design: Prospective analysis of 138 general surgical operative notes identified over a 2-week period. We created a 26-point core checklist incorporating both RCS (Eng.) 2014 and GMC " Good Medical Practice " 2013 guidance. We then audited elective and emergency operative documentation against this standardised proforma. Data collected was subsequently evaluated once compiled onto a computerised spreadsheet (Table 1 ). Strategy for change: Our findings were presented at the weekly departmental meeting, where we emphasised the need for operative note improvement. Proposed interventions were then implemented at the earliest opportunity. In particular, details not previously recorded, yet strongly advocated, by the RCS Eng. were promoted (e.g. anticipated blood loss, DVT prophylaxis etc.). Measurement of improvement: We intend to re-audit operation notes in 2–3 months' time, using an identical proforma to record data, once the proposed interventions have been implemented. We will determine whether results attained are statistically significant by calculating p-values and using simple statistical data analysis. Effects of changes: We anticipate enhanced operative note standards as a result of introducing the proposed interventions. Our aspiration is to generate discussion in computerised documentation of surgeries and inspire greater numbers of surgeons to make use of electronic systems to ensure operative notes are both standardised and increasingly legible. Lessons learnt: Surgeons were receptive to this study's findings and were genuinely keen to improve upon their own operative documentation. Concerns were raised as to whether certain areas of documentation advised by the RCS Eng. are applicable to the paediatric populace e.g. DVT prophylaxis. This highlighted the importance of considering your patient cohort when formulating an operative note template. Message for others: We envisage the future of operative notes to be an electronic format. However, until this is achieved we recognise that the majority of surgeons will continue to use our current paper-based arrangement. Thus, we believe that typed operative documentation (using the methods described above) is an acceptable platform towards ameliorating the existing Trakcare system.